An 8 month slow slip event triggers progressive nucleation of the 2014 Chile megathrust. Issue 9 (8th May 2017) - Socquet, Anne; Valdes, Jesus Piña; Jara, Jorge; Cotton, Fabrice; Walpersdorf, Andrea; Cotte, Nathalie; Specht, Sebastian; Ortega‐Culaciati, Francisco; Carrizo, Daniel; Norabuena, Edmundo
Abstract: The mechanisms leading to large earthquakes are poorly understood and documented. Here we characterize the long‐term precursory phase of the 1 April 2014 M w 8.1 North Chile megathrust. We show that a group of coastal GPS stations accelerated westward 8 months before the main shock, corresponding to a M w 6.5 slow slip event on the subduction interface, 80% of which was aseismic. Concurrent interface foreshocks underwent a diminution of their radiation at high frequency, as shown by the temporal evolution of Fourier spectra and residuals with respect to ground motions predicted by recent subduction models. Such ground motions change suggests that in response to the slow sliding of the subduction interface, seismic ruptures are progressively becoming smoother and/or slower. The gradual propagation of seismic ruptures beyond seismic asperities into surrounding metastable areas could explain these observations and might be the precursory mechanism eventually leading to the main shock. Key Points: Westward acceleration of coastal GPS stations 8 months before the main shock reveals a M w 6.5 aseismic slow slip event on fault interface Interface foreshocks underwent a diminution of their radiation at high frequency, suggesting a modification in source parameters Slow sliding of subduction interface and gradual enlarging of seismic ruptures are the precursory mechanisms leading to the main shock